1996
DOI: 10.1093/oxfordjournals.aje.a008879
|View full text |Cite
|
Sign up to set email alerts
|

Entomologic Index for Human Risk of Lyme Disease

Abstract: An entomologic index based on density estimates of Lyme disease spirochete-infected nymphal deer ticks (lxodes scapularis) was developed to assess human risk of Lyme disease. The authors used a standardized protocol to determine tick density and infection in numerous forested sites in six Rhode Island towns. An entomologic risk index calculated for each town was compared with the number of human Lyme disease cases reported to the Rhode Island State Health Department for the same year. A strong positive relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
126
0
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(130 citation statements)
references
References 11 publications
3
126
0
1
Order By: Relevance
“…For example, a study that measured DIN in forested areas in six Rhode Island towns found that DIN explained 97% of the variation in incidence among those towns. 9 However, most of our study sites were not located in residential areas, and the incidence data corresponded to a much broader range relative to the acarological data, which increases the variance in the relationship between mDIN and incidence. Last, geographical differences in Lyme disease control efforts at the residential or personal level could also contribute to variation in the relationship between mDIN and human incidence.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…For example, a study that measured DIN in forested areas in six Rhode Island towns found that DIN explained 97% of the variation in incidence among those towns. 9 However, most of our study sites were not located in residential areas, and the incidence data corresponded to a much broader range relative to the acarological data, which increases the variance in the relationship between mDIN and incidence. Last, geographical differences in Lyme disease control efforts at the residential or personal level could also contribute to variation in the relationship between mDIN and human incidence.…”
Section: Discussionmentioning
confidence: 92%
“…Three previous studies have shown a positive relationship between human cases and the density of B. burgdorferi-infected ticks, but these studies were limited in geographic scope to Connecticut and Rhode Island, which are both states with very high prevalence. [9][10][11] Another two studies showed a positive correlation between tick abundance and human cases, again focusing on specific regions (Wisconsin 12 and Westchester, New York 13 ). Two more location-specific studies have examined the link between numbers of ticks sampled by passive surveillance and cases in Rhode Island and Maine.…”
Section: Introductionmentioning
confidence: 99%
“…For most vector-borne pathogens, no human vaccines exist; the main approach for reducing the public's risk for disease transmission is vector control. Vaccines directed at animal reservoirs provide additional opportunities to intervene in natural cycles and reduce disease risk by the criterion of number of infected vectors (4). Successful vaccination would decrease the availability of infected hosts to vectors, resulting in a lower proportion of vectors that are infected, and thus, a lower probability of pathogen transmission to humans.…”
mentioning
confidence: 99%
“…More recently, Mather and others 28 proposed an ''entomological risk index'', calculated by multiplying the number of ticks collected per person-hour by the proportion of ticks infected. We chose a technique based on area surveyed rather than collection time so that estimates of tick abundance would not be affected by collectors' travel rates.…”
Section: Discussionmentioning
confidence: 99%